THE EFFECT OF ILOPROST AND NDGA IN ISCHEMIA REPERFUSION INJURY IN RAT-LIVER - YEGEN, ŞEVKET CUMHUR (ELSEVIER SCI LTD, 1992)
In this study, the effects of iloprost (ZK 36374) and NDGA on warm ischemia and reperfusion injury in rat liver were investigated. Rats were given isotonic saline (control group), iloprost 25 mug/kg i.v. (group II) just before warm ischemia or NDGA 10 mug/kg i.v. (group III) 5 min before reperfusion or the same drug were given together (group IV). Serum SGOT, SGPT, and LDH values and tissue malonedialdehyde (MDA), gluthathione (GSH), prostaglandin (PGE2, and leukotriene (LT)C4 levels were determined after ischemia-reperfusion injury. Histopathologic examination of the liver was carried out under the light microscope. The serum SGOT, SGPT and LDH levels improved significantly in groups II, III, and IV when compared with the control group (p < 0.05). There was a significant decrease (p < 0.05) in tissue MDA levels and significant increase (p < 0.05) in tissue GSH levels in group I, when compared with group IV and the control groups. The values did not differ significantly in group IV when compared to controls. The LTC4/PGE, ratio was low and histologic findings were worse in group III. In conclusion, iloprost was found to,be beneficial in preventing the ischemia-reperfusion injury in the rat livers. NDGA, either by direct toxic effector by Shifting the arachidonic acid metabolism to the cyclooxygenase route, was not found to be as effective. Iloprost and NDGA did not exert a synergistic effect.
Keywords: FREE-RADICALS; LEUKOTRIENES; GLUTATHIONE; BIOSYNTHESIS; PROSTACYCLIN; METABOLISM